Akulturasi Islam dan Budaya Masyarakat Lereng Merapi Yogyakarta: Sebuah Kajian Literatur - Arief Aulia Rachman (JURNAL INDO-ISLAMIKA, 2012)
This essay attempts to discuss how Islam was perceived and developed in Java, within Lereng Merapi society in particular, and how Islam had influenced the local culture in one side and how it had been influenced by the local culture in another. This essay argues that there have been strong acculturation between Islam and local culture. It aslo argues that the spread of Islam in this society had taken long periods as Islam did not counter local culture. It, instead, penetrated with persuasive approach by adopting local culture and preserving pristine Islamic doctrines.